2020
DOI: 10.1038/s41598-020-78863-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the stability of 70 housekeeping genes during iPS reprogramming

Abstract: Studies on induced pluripotent stem (iPS) cells highly rely on the investigation of their gene expression which requires normalization by housekeeping genes. Whether the housekeeping genes are stable during the iPS reprogramming, a transition of cell state known to be associated with profound changes, has been overlooked. In this study we analyzed the expression patterns of the most comprehensive list to date of housekeeping genes during iPS reprogramming of a mouse neural stem cell line N31. Our results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…The data obtained indicate that there is no universal HKG both for different brain tissues of one organism and for similar tissues of different organisms. This conclusion is supported by other studies: researchers must select and validate a set of reference genes for each specific cell line [ 41 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The data obtained indicate that there is no universal HKG both for different brain tissues of one organism and for similar tissues of different organisms. This conclusion is supported by other studies: researchers must select and validate a set of reference genes for each specific cell line [ 41 ].…”
Section: Discussionsupporting
confidence: 66%
“…However, in 2020, the same group of scientists, when analyzing HKGs in induced pluripotent stem cells of the same lineage, concluded that GAPDH has a highly variable expression during reprogramming. This gene is not attractive as a reference gene for the analysis of expression in works related to the process of fibroblast reprogramming [ 41 ]. The authors point out that the way the primers were selected changed from the first publication to the second.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses showed that different reference genes revealed no stable expression during the development of the human inner ear. Using one single reference gene is generally not recommended, as discussed in Vandesompele et al (2002) [57], and Panina et al (2020) [58]. Normalization against one reference gene may lead to misleading results.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoglycerate mutase 1 (PGAM-1) expresses an enzyme responsible for catalyzing 3-phosphoglycerate (3-PGA) to 2-phosphoglycerate (2-PGA), playing an essential role in glycolysis. It is also ubiquitously distributed in multiple cell types [ 52 , 53 ]. Shared characteristics related to vital processes in the organism, such as glycolysis, immune response, protein folding and cell structure, especially due to applicability to multiple species and most tissues, bring up those 6 genes as relevant targets to investigate as suitable reference genes in our study.…”
Section: Discussionmentioning
confidence: 99%